Barriers to healthcare for transgender individuals. Issue 2 (April 2016) - Safer, Joshua D.; Coleman, Eli; Feldman, Jamie; Garofalo, Robert; Hembree, Wylie; Radix, Asa; Sevelius, Jae
Abstract : Purpose of review: Transgender persons suffer significant health disparities and may require medical intervention as part of their care. The purpose of this manuscript is to briefly review the literature characterizing barriers to healthcare for transgender individuals and to propose research priorities to understand mechanisms of those barriers and interventions to overcome them. Recent findings: Current research emphasizes sexual minorities' self-report of barriers, rather than using direct methods. The biggest barrier to healthcare reported by transgender individuals is lack of access because of lack of providers who are sufficiently knowledgeable on the topic. Other barriers include: financial barriers, discrimination, lack of cultural competence by providers, health systems barriers, and socioeconomic barriers. Summary: National research priorities should include rigorous determination of the capacity of the US healthcare system to provide adequate care for transgender individuals. Studies should determine knowledge and biases of the medical workforce across the spectrum of medical training with regard to transgender medical care; adequacy of sufficient providers for the care required, larger social structural barriers, and status of a framework to pay for appropriate care. As well, studies should propose and validate potential solutions to address identified gaps.